Effectiveness of the Cheap Food Movement Program in Improving Food Security in Kuningan District - Siti Khumayah; Euis Nurohmah (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
Kuningan District, as an agricultural area, still faces problems of price stability and food affordability, especially ahead of religious holidays when food prices surge. To address these issues, the local government, through the Kuningan District Food Security and Agriculture Agency, has implemented the Cheap Food Movement program as part of the national policy to control inflation and strengthen food security. This study aims to analyze the effectiveness of the implementation of the Cheap Food Movement in improving food security, with a focus on accessibility, price affordability, and public perception. Data analysis refers to J.P. Campbell's (1970) theory of effectiveness, which includes five indicators: program success, target success, program satisfaction, input-output suitability, and overall goal achievement. This study uses a qualitative descriptive method with data collection through direct observation, interviews, and documentation, as well as applying source and method triangulation to test data validity. The results of the study indicate that the Cheap Food Movement program contributes to improving food access and affordability and encourages an increase in the Food Security Index (IKP), although there are several aspects that need improvement, such as target data integration, funding consistency, and budget sustainability to optimize program effectiveness.